2006
DOI: 10.1021/ja055962q
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Protein Dynamics:  A Simulation Analysis of Interprotein Vibrations and the Boson Peak at 150 K

Abstract: An understanding of low-frequency, collective protein dynamics at low temperatures can furnish valuable information on functional protein energy landscapes, on the origins of the protein glass transition and on protein-protein interactions. Here, molecular dynamics (MD) simulations and normal-mode analyses are performed on various models of crystalline myoglobin in order to characterize intra- and interprotein vibrations at 150 K. Principal component analysis of the MD trajectories indicates that the Boson pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 60 publications
4
55
1
Order By: Relevance
“…At low frequencies (in the THz, or meV, range), amorphous solids exhibit a pronounced excess of vibrational states over the Debye level, an excess known as the boson peak (44)(45)(46)(47)(48)(49)(50)(51). This boson peak is displayed equivalently here (Figure 3, a-d) for the three proteins around 1-3 meV, as already observed in many enzymes (13,37,(52)(53)(54)(55)(56)(57). This indicates that the presence of soft modes is not affected by the mutations.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…At low frequencies (in the THz, or meV, range), amorphous solids exhibit a pronounced excess of vibrational states over the Debye level, an excess known as the boson peak (44)(45)(46)(47)(48)(49)(50)(51). This boson peak is displayed equivalently here (Figure 3, a-d) for the three proteins around 1-3 meV, as already observed in many enzymes (13,37,(52)(53)(54)(55)(56)(57). This indicates that the presence of soft modes is not affected by the mutations.…”
Section: Resultssupporting
confidence: 72%
“…Data for the H subunit are not shown, as the mutation is found to have no effect on the force constants of its residues. between the increase of 〈u 2 〉 fluctuations, defining the dynamical transition, and the harmonic excess modes contained in the vibrational density of states and the boson peak (13).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the density of phonon states cannot be gathered from spectral hole burning (SHB) or FLN but is obtained separately by using the complementary method of inelastic neutron scattering (INS) as shown by Pieper et al (2004). INS studies revealed that the density of phonon states appears to be relatively similar for many different proteins (Orecchini et al, 2002;Paciaroni et al, 2003;Pieper et al, 2004;Kurkal-Siebert and Smith, 2006) but the spectral form was shown to vary with protein size (see e.g. Refs.…”
Section: Pigment-protein Interactionmentioning
confidence: 99%
“…Refs. Orecchini et al, 2002;Kurkal-Siebert and Smith 2006) and due to interaction with the solvent (see e.g. Refs.…”
Section: Pigment-protein Interactionmentioning
confidence: 99%
“…The combination has proven to be effective for biological systems as shown by numerous studies. MD simulations were used to decompose measured spectra into contributions from different types of motions [14][15][16][17][18][19] and to study the effect of instrument resolution. 20 Previous MD simulations of the purple membrane for comparison with energy-resolved neutron scattering spectra 21,22 showed promising results but did not contain atomic models of the lipid environment and solvating water.…”
Section: Introductionmentioning
confidence: 99%